Proteomic and toxicological characterization of the venoms of the most enigmatic group of rattlesnakes: The long-tailed rattlesnakes - Neri Castro, Edgar (2022)
The most enigmatic group of rattlesnakes is the long-tailed rattlesnake group, consisting of three species: Crotalus ericsmithi, Crotalus lannomi and Crotalus stejnegeri. These species have been the least studied rattlesnakes in all aspects, and no study on the characterization of their venoms has been carried out to date. Our main objective was to investigate the proteomic composition, as well as some of the biochemical and toxic activities of these venoms, and their neutralization by commercial antivenom. The venom proteome of C. ericsmithi mainly contains metalloproteinases (SVMP; 49.3%), phospholipases A2 (PLA2; 26.2%), disintegrins (Dis; 12.6%), and snake venom serine proteases (SVSP; 6.8%), while C. lannomi venom mainly consists of SVMP (47.1%), PLA2 (19.3%), Dis (18.9%), SVSP (6%) and l-amino acid oxidase (LAAO; 2.6%). For these venoms high lethality was recorded in mice, the most potent being that of C. lannomi (LD50 of 0.99 μg/g body weight), followed by C. ericsmithi (1.30 μg/g) and finally C. stejnegeri (1.79 μg/g). The antivenoms Antivipmyn® from SILANES and Fabotherapic polyvalent antiviperin® from BIRMEX neutralized the lethal activity of the three venoms. Although this group of snakes is phylogenetically related to the C. viridis group, no neurotoxic components (crotoxin or crotoxin-like proteins) common in rattlesnakes were found in their venoms. This study expands current knowledge on the venoms of understudied snake species of the Mexican herpetofauna